FORMATION OF INDEPENDENT EDUCATION IN STUDENTS OF HIGHER EDUCATION (Academia Science Repository, 2023)
This article successfully analyzes independent thinking is social because every idea is tested and shared with others. The active life position of the student is especially evident when comparing previously existing knowledge and concepts with newly acquired knowledge. Allows students to customize any technology to suit the structure, functions, content, goals, and objectives of teaching in a specific group of students.